An assessment of circulating biomarkers and germline genetic variants in predicting chemotherapy associated mucositis in Ewing sarcoma - Pawan Gulati; Vickyanne Carruthers; Claire Hutton; Chloe Cassidy; Edward B. Amankwatia; Séréna Pascual; Electra Florence; Tsegay G. Gebru; Andrea L. Jorgensen; Alastair Greystoke; Guy Makin; Martin G. McCabe; et al. (EJC Paediatric Oncology)
Background: Treatment of Ewing sarcoma is associated with severe toxicities including chemotherapy-induced mucositis. Here we investigated the role of circulating biomarkers and genetic factors in predicting mucositis severity in Ewing sarcoma. Methods: Blood samples were collected from 111 Ewing sarcoma patients during treatment. Circulating total CK18 and FLT3 ligand concentrations were measured in plasma. Germline DNA was used to investigate associations between genetic variants and mucositis severity. Results: An increase in median tCK18 levels was observed during cycle 1, from 189 (86−736) U/L at cycle 1 day 1 pre-chemotherapy to 311 (141–1138) U/L on cycle 1 day 2–5 (p = 0.0001). Patients experiencing a ≥ 1.3-fold increase in tCK18 at 48–120 hours after administration of the first cycle had a higher likelihood of developing grade 3 mucositis in any cycle (p = 0.044). Genetic analysis revealed an association between a gene set associated with chemotherapy induced severe mucositis and differentially expressed genes set for minor salivary gland (p = 4.12 ×10−4) and esophageal mucosa (p = 1.55 ×10−5). Discussion: Early increases in circulating CK18 levels correlated with grade 3 mucositis. Genome-wide association analysis highlighted genes that may be associated with mucositis pathology, offering insights into biological mechanisms underlying susceptibility.